Laboratory investigation of soil reinforcement using shredded waste plastic bottles - Chim Jin, Dercio José Pinto (Department of Civil Engineering, 2019)
Plastic bottles were first used commercially in 1947 but remained relatively expensive until the early 1960s when high-density polyethylene was introduced, with its attractive characteristics such as being strong, lightweight, durable, cheap, and resistance to breakage. Decomposition of plastic bottles or other plastic products can last from 400 to 1000 years; before this process happens, the plastic waste becomes a problem to the environment continuing to clog our waterways, forest, oceans and others natural habitats. As the capacity of landfills decrease and urbanization leads to rapid growth rates in the human population, either in Africa or any part of the world, this concern brought forward the need for this study. The research aimed to present an end-use solution for plastic bottles by investigating the feasibility of utilizing the plastic bottles as reinforcing elements in problematic soils encountered in the construction industry. In South Africa, plastic bottle waste has continued to increase despite efforts by government in the form of new waste legislation and taxes on plastic bottles. Hence, there is a need to find alternative uses for plastic bottle waste. The use of plastic bottle waste shreds as a soil reinforcement material in geotechnical engineering applications can help mitigate the disposal problems associated with plastics. In this study, a series of direct shear tests were conducted to examine the effect of plastic waste shredded pieces on the engineering properties of Cape Flats and Klipheuwel Sand. The shredded plastic bottles that were used for this study were sourced from Kaytech (supplier and manufacturer of Geosynthetics) in South Africa. The research was done to utilize this plastic through the inclusion of shredded plastic bottles as a form of soil reinforcement. The effects of introducing polyethylene shreds cut from used plastic bottles on the settlement parameters were investigated. It was found that presence of plastic shreds improved the shear strength parameters of the sand soil and they tend to improve further with increasing in plastic shred dosage. The cohesion reached its maximum value for both sands at a shred dosage of 30% by dry mass of the soil.